2010
DOI: 10.1183/09031936.00069910
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aerobic exercise capacity and procedure-related factors in lung cancer surgery

Abstract: Over the past decades, major progress in patient selection, surgical techniques and anaesthetic management have largely contributed to improved outcome in lung cancer surgery. The purpose of this study was to identify predictors of post-operative cardiopulmonary morbidity in patients with a forced expiratory volume in 1 s ,80% predicted, who underwent cardiopulmonary exercise testing (CPET).In this observational study, 210 consecutive patients with lung cancer underwent CPET with completed data over a 9-yr per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 50 publications
(56 reference statements)
0
48
0
1
Order By: Relevance
“…A total of 21 hospital-based cohort studies (12 prospective, 9 retrospective) were included in this review with a total of 4957 patients that underwent CPEX testing prior to lung (12)(13)(14)(15)(16)(17), colorectal (18-20), liver (21-23), oesophagogastric (24-26), bladder (27)(28)(29) and pancreas resection (30-32) ( Figure 1). No studies were found in breast, brain or lymphoma cancers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 21 hospital-based cohort studies (12 prospective, 9 retrospective) were included in this review with a total of 4957 patients that underwent CPEX testing prior to lung (12)(13)(14)(15)(16)(17), colorectal (18-20), liver (21-23), oesophagogastric (24-26), bladder (27)(28)(29) and pancreas resection (30-32) ( Figure 1). No studies were found in breast, brain or lymphoma cancers.…”
Section: Resultsmentioning
confidence: 99%
“…A review of these abstracts identified 23 potentially relevant papers. Six studies met the inclusion criteria and were included in this review (12)(13)(14)(15)(16)(17). All were observational cohort studies (2 prospective, 4 retrospective), with a total of 2814 patients from hospitals within Europe and the USA.…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…2 Peak oxygen uptake (peak V O 2 ), as determined during cardiopulmonary exer-cise testing (CPET), is the reference method to evaluate exercise capacity and predicts early postoperative complications as well as long-term outcome. [3][4][5][6] Besides aging, comorbidities such as COPD, diabetes mellitus, hypertension, peripheral artery disease, and heart failure are highly prevalent in these patients and may all limit aerobic exercise capacity. 7 Moreover, sedentary behavior and the inflammatory component associated with cancer contribute to muscle wasting and decreased peripheral aerobic metabolic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Sympathetic activity may be assessed via muscle microneurography, baroreflex sensitivity, and HR recovery [20,21]. Each of these methods reflects a different aspect of the ANS and is useful in the assessment of peak oxygen uptake, which is predictive of cardiac and pulmonary mortality [22]. Among these, HR recovery is the most promising method.…”
Section: Discussionmentioning
confidence: 99%